Odontogenic Keratocyst of Coronoid process presenting as an infratemporal mass (Bangladesh Journal of Otorhinolaryngology, 2015)
A pediatric patient presented with facial swelling. CT scans showed a left infratemporal mass with erosion of coronoid process and normal dentition. CT guided FNAB suggested the possibility of odontogenic keratocyst. The mass was excised by a transzygomatic approach. A four year followup has not shown any recurrence. The possibility of odontogenic keratocyst needs to be considered while evaluating infratemporal fossa swellings. DOI: http://dx.doi.org/10.3329/bjo.v20i2.22028 Bangladesh J Otorhinolaryngol; October 2014; 20(2): 106-108